Taxonomic revision of Veronica subsection Pentasepalae (Veronica, Plantaginaceae sensu APG III) - Rojas-Andrés, Blanca M.; Martínez-Ortega, M. Montserrat (Phytotaxa, 2016)
Veronica subsect. Pentasepalae is a monophyletic group of perennial herbs distributed mainly in Europe, with a few species reaching Siberia and one N Africa. Since its first description by Bentham in 1846, both the circumscription of the subsection and the species boundaries have been subject to controversy. The first complete taxonomic revision of V. subsect. Pentasepalae is presented here in the light of recent phylogenetic analyses based on DNA sequence data and ploidy level information. For this work ca. 2900 sheets lodged at 63 herbaria were studied and approximately 500 populations were visited directly in the field. Detailed morphological descriptions, illustrations, notes on habitat preferences, phenology, chromosome numbers and distribution maps are provided, as well as an identification key to all species. Twenty-two taxa are recognized for V. subsect. Pentasepalae: 17 species, four subspecies and one variety.